Strategies, ideas, concepts: Informal discussion with Papcsák Ferenc, the mayor of zugló and with barta ferenc, the chief municipality architect of zugló (4D Journal of Landscape Architecture and Garden Art, 2013)
Our target area is found along the Rákos-creek that has had a great importance in the development of the agglomeration area of the Budapest Region previously. In the middle of the 20th century the creek had been regulated and its role in the urban fabric has slowly reached its current state. The area evolved into an ambiguous and fragmented urban fabric, where various residential typologies and slowly transforming brownfield industrial zones are alternating.
Keywords: zugló; Papcsák Ferenc